Perfil físico-químico e aspectos microbiológicos do queijo tipo coalho comercializado em Estados do Nordeste do Brasil - Sousa, Andréa Zilá Barroso de (2010)
The cheese curd is a typical product of the Northeastern part of Brazil. Despite of its great representation, the studies involving the physical, chemical and microbiological attributes that characterize its quality are still scarce. The purpose of the job was studying the physical, chemical and microbiological characteristics of the cheese curd commercialized in six of the northeastern Brazilian states. There were commercialized 104 cheese curd samples at the states of Pernambuco (20), Piauí (10), Ceará (24), Rio Grande do Norte (20), Sergipe (20) and Paraíba (10). 50 of the 104 samples had been examinated, while 54 of them had not. The physical-chemical characterization was realized (pH, water activity, humidity and acidity), as well as the microbiological. For the pH parameter of the examinated samples there were variations from 5,68±0,29 to 6,30±0,30 for the examinated QCI and 5,18±0,15 to 6,22±0,37 to the QCA. The water activity varied from 0,911±0,012 to 0,963±0,007 for the examinated QCI and 0,892±0,036 to 0,962±0,009 for homemade cheese curds. Humidity had variation from 14,38 ± 3,53 to 24,08±10,87 for the examinated cheese curds and from 15,00±2,00 to 29,38±15,79 for the home produced cheese curds. The percentual acidity expressed in lactic acid varied from 0,16% ± 0,22 to 0,74 ± 0,17 of lactic acid for the examinated cheese curds and from 0,12±0,01 to 1,01±0,24 for the homecrafted cheese curds. There were also searches for Staphylococcus aureus, Coliformes Termotolarentes and Salmonella. Only five of the 104 samples followed the pattern stabilished by the government for Staphylococcus aureus and only four were appropriated for human consumption, for their count was following the established pattern of the government. 72 of the 104 examinated samples were according to the pattern established by ANVISA for Coliformes Termotolerantes, and only one of the samples detected Salmonella. There was no valuable difference between the examinated and non-examinated samples for Coliformes Termotolerantes. There was not a significative difference between the analysed and non-analysed samples for Staphylococcus aureus. From such results, it is noticeable that the samples had a bad quality and were, at its biggest part, inappropriate for human consumption, what justifies the importance of offering orientation about the raw material quality to the producers, as well as adequate hygiene conditions and manipulation in the homemade cheese production; and more attention and supervision by the responsible industries by implementing strict control in the processing of the product